On the curvatures of (r + 1)-dimensional generalized time-like ruled surface - Bektaş, Mehmet (My University, 2003)
In this paper, we obtain some relationships between the curvatures of (r + 1)-dimensional generalized time-like ruled surfaces. We also calculate the drall of a generalized time-like ruled surfaces when the base curve is taken as an orthogonal trajectory of the generated spaces.
Keywords: Minkowski space; Time-like ruled surface